Consumer Demographics and Behaviour - Martins, Jo M. author. aut Link
XXII, 214 p.
Keywords: This is the book that market strategists have been waiting for to position themselves in global markets and take advantage of the opportunities that demographic bonuses and deficits offer to them and their products. It is also a book for teachers and students of consumer behaviour to grasp the importance of the life cycle as a framework that shapes the demand for goods and services determined by changes in social, economic and physical functioning. It gives insights into gendered consumer behaviour and cohort effects. It presents a range of views on consumer behaviour and how demographic perspectives enhance these perspectives. The book offers conceptual and analytical tools that can be used in the assessment of population characteristics as determinants of market size, composition and potential for a variety of products. It offers organising frameworks as well as empirical evidence of consumer behaviour in clusters of markets, with different rates of population growth and age distribution that affect consumers’ priorities and demand for basic and progressive commodities. The book shows commonalities as well as differences in consumer behaviour arising from different cultures and social customs. It uses analytical tools that are explained and accessible to readers with a range of competences. It is a book that can give a better understanding of consumer behaviour and market opportunities to the practitioner. It can also be used for the instruction of students in demography, consumer behaviour and marketing. .